SAT0502 LONG-TERM OBSERVATIONAL SAFETY SURVEILLANCE OF GOLIMUMAB TREATMENT FOR POLYARTICULAR JUVENILE IDIOPATHIC ARTHIRTIS—AN INTERIM ANALYSIS. (2nd June 2020) - Horneff, G.; Zimmer, A.; Minden, K.; Hospach, T.; Weller-Heinemann, F.; Hansmann, S.; Kuemmerle-Deschner, J.; Fasshauer, M.; Hofmann, N.; Koessel, H.; Foeldvari, I.; Mrusek, S.; et al.
Abstract : Background: Golimumab (GOL) is approved for treatment of polyarticular juvenile idiopathic arthritis (pJIA) in patients 2 years and older. Data on long-term safety in this indication are limited. Objectives: Prospective monitoring of long-term safety and effectiveness of GOL in routine care using the German BIKER registry. Methods: In this non-interventional study baseline and safety parameters were compared between patients initiating GOL and contemporary matched control cohorts starting either an alternative TNF inhibitor (TNFi) or methotrexate (MTX) without exposure to a biologic. Efficacy outcomes were JADAS10, JIA ACR scores, joint counts and Childhood Health Assessment Questionnaire disability-index (CHAQ-DI). Safety assessments were based on adverse event (AE) reports. Results: From 2016 to 2019, 55 patients initiating GOL have been recruited and matched to 110 patients starting alternative TNFi and 47 biologic-naïve patients. Patients starting GOL had a longer disease duration (6.8y vs. 4.1 y and 1.0y; p<0.0001) and use of GOL was significantly more often second-line (85% vs 31% and 0%, p<0.0001). Disease activity was lower at baseline compared to MTX patients as indicated by active joint counts, JADAS10 and concomitant steroid use. Otherwise they were comparable with patients treated with other TNFi (Table 1 ). In GOL treated patients a marked clinical response was noted at 6 months and beyond demonstrated by a significant decrease of the mean JADAS 10 from 11.3 to 6.4 (p=0.0008), as well as JIA ACR 30/50/70/90 response rates of 56/56/35/21%. JADAS remission and minimal disease activity was observed in 18% and 47% after 6 months and in 29% and 43% of patients after 12 months. Rates of AE, SAE and infectious AE were comparable between the GOL cohort (96, 4.2 and 12.8/100PY), the alternative TNFi cohort (114, 5.4 and 11.8/100PY) and the MTX cohort (107, 2.7 and 24.5/100PY). SAE reported in the GOL cohort were uveitis and JIA flare (each 1). Two serious infections, both influenza, were reported in the alternative TNFi cohort, none in the GOL cohort. No case of pregnancy, malignancy or death was reported. Conclusion: Interim results from this ongoing safety surveillance study indicate acceptable safety and tolerability of GOL in pJIA that is comparable to treatment with alternative TNFi or MTX. The long-term effectiveness data reinforce the established efficacy of GOL in pJIA treatment. Disclosure of Interests: Gerd Horneff Grant/research support from: AbbVie, Chugai, Merck Sharp & Dohme, Novartis, Pfizer, Roche, Speakers bureau: AbbVie, Bayer, Chugai, Merck Sharp & Dohme, Novartis, Pfizer, Roche, Angela Zimmer: None declared, Kirsten Minden Consultant of: GlaxoSmithKline, Sanofi, Speakers bureau: Roche, Toni Hospach: None declared, Frank Weller-Heinemann: None declared, Sandra Hansmann Consultant of: Advisory board Novartis Pharma, Jasmin Kuemmerle-Deschner Grant/research support from: Novartis, Sobi, Consultant of: Novartis, Sobi, Speakers bureau: Novartis, Sobi, Maria Fasshauer Consultant of: Shire, CSL Behring, Nadja Hofmann: None declared, Hans Koessel: None declared, Ivan Foeldvari Consultant of: Novartis, Sonja Mrusek: None declared, Daniel Windschall Speakers bureau: Abbvie, Nils Onken: None declared, Markus Hufnagel: None declared, Dirk Foell Grant/research support from: Novartis, Sobi, Pfizer, Speakers bureau: Novartis, Sobi, Normi Brueck: None declared, Prasad Oommen Consultant of: Novartis, Frank Dressler: None declared, Astrid Helling-Bakki: None declared, Ariane Klein Consultant of: Celgene